PATTERN OF SEXUALLY TRANSMITTED DISEASES IN HAZARA DIVISION - Khan, Imranullah; Rizvi, Kamran; Javed, Muhammad; Shah, Syed Humayun (Journal of Ayub Medical College Abbottabad, 1995)
A retrospective study was done involving 185 patients with sexually transmitted diseases, the aim being to know the pattern of sexually transmitted diseases, male to female ratio, common age groups, marital status and sources of infection. Gonorrhoea was the most common sexually transmitted disease. There were 32 cases of genital warts, 16 cases of non-gonococcal urethritis, 10 cases of genital molluscurn contagiosum, 9 cases of herpes genitalis, 8 cases of syphilis, 6 cases of lymphogranuloma venereum and 2 cases of chancroid. Of 185 cases only 6 were females. Majority of the patients were between 20-40 years of age. Most of the patients (about 64%) were married and had acquired infections from prostitutes, married women and eunuchs.